Proses Pemecahan Masalah Siswa Impulsif pada Materi Program Linier - Nourma Pramestie Wulandari; Ulfa Lu'luilmaknun (Pendidikan Matematika FKIP Universitas Mataram, 2022)
The aim of this research is to describe the problem solving process of impulsive students on linear programs. The subject of this research are 2 students that already learned about linear programs. The problem solving process of impulsive student are: (1) at first, student gathering information, then the information are being translated to mathematics model without making any table, (2) there is no problem modification therefore objective function are incorrect, (3) determining coordinate points to draw graphic and feasible solution, (4) determining intersection using substitution method and elimination method, (5) conducting the corner point method. However, the result are incorrect because objective function are incorrect